Information searching behaviors among Vietnamese students during first wave of the COVID-19 pandemic - Vo Van, Thang (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objective: This study aims to describe the COVID-19 related information searching behaviors and the relationship between those behaviors and the satisfaction with the COVID-19 related information searched on the Internet among university students during first wave of the COVID-19 pandemic in Vietnam. Methods: A cross-sectional study was conducted by a web-based survey from April 25, 2020 to May 9, 2020. Convenient sample with the method of snowball sampling was applied, 1003 students were obtained totally. Multivariable logistic regression model was used to identify the associations between those behaviors and the satisfaction with the COVID-19 related information searched on the Internet. Results: Search engines were the most popular sources used for online COVID-19 information seeking (95.3%), followed by Social media (92.4%) and News portals (91.6%). About 90% of participants searched the information related to the current spread of the coronavirus, followed by symptoms of the COVID-19 (81.8%) and individual measures to protect against infection (81.9%). Vietnamese remains the main language of the sources with 70.3% of participants used. There’s 45.8% of participant satisfied about the COVID-19 related information. The group of participants who sought information about prevention was 0.47 times less dissatisfied than the group that did not search. Conclusion: There are significant associations between searching topics related to prevention and the COVID-19 related information satisfaction searched on the Internet. These results highlight the need for providing efficient information related to the COVID-19 pandemic as well as seriously consider focusing more on social media to better bring official information to the public.